2020
DOI: 10.1038/s41538-020-00070-3
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the molecular complexity of brewing

Abstract: The compositional space of a set of 120 diverse beer samples was profiled by rapid flow-injection analysis (FIA) Fourier transform ion cyclotron mass spectrometry (FTICR-MS). By the unrivaled mass resolution, it was possible to uncover and assign compositional information to thousands of yet unknown metabolites in the beer matrix. The application of several statistical models enabled the assignment of different molecular pattern to certain beer attributes such as the beer type, the way of adding hops and the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 52 publications
5
18
0
Order By: Relevance
“…Such compounds that show strong evidence for the use of wheat (Pihlava and Kurtelius, 2016;Pieczonka et al, 2020) and corn (Fenz, 1991;Fenz et al, 1992) in brewing have been adequately described and have been confirmed in our study. In addition, numerous derivatives of these compounds could be characterized.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Such compounds that show strong evidence for the use of wheat (Pihlava and Kurtelius, 2016;Pieczonka et al, 2020) and corn (Fenz, 1991;Fenz et al, 1992) in brewing have been adequately described and have been confirmed in our study. In addition, numerous derivatives of these compounds could be characterized.…”
Section: Discussionsupporting
confidence: 87%
“…As reported before (Pieczonka et al, 2020) reinforces the presence of a carboxylic acid group of these compounds on the molecular structure level. Based on this annotation, known to be specific for the use of corn (Fenz, 1991) changes equivalent to hydroxylation, hydrogenation, methoxylation or water addition form a network of masses specific to corn.…”
Section: Direct Infusion Fourier Transform Ion Cyclotron Mass Spectrometrysupporting
confidence: 86%
See 3 more Smart Citations